Pola Bakteri Aerob dan Uji Kepekaan Antibiotik pada Urine Pasien dengan Kateter Uretra di RSU Gmim Pancaran Kasih Manado - Eudia Marlina Kawoka; Fredine Esther Silvana Rares; Olivia Amelia Waworuntu (Syntax Corporation Indonesia, 2025)
Bacteria are prokaryotic organisms, many of which are part of the normal flora in the human body without causing infection. The infection pattern caused by this aerobic bacteria can very depending on factors such as the duration of catheter use, the patient’s health condition, and hygiene levels. Catheter-Associated Urinary Tract Infections (CAUTI) is one of the most common infections in the ICU and contribute to increased mortality and morbidity rates. Objective: To determine the aerobic bacterial patterns in urethral catheters and their antibiotic susceptibility at Pancaran Kasih General Hospital, Manado. Method: This study used a descriptive observational design with a cross-sectional approach to analyze the aerobic bacterial patterns and antibiotic susceptibility in the urine of patients with urethral catheters at GMIM Pancaran Kasih General Hospital, Manado. Results: Samples were taken from patients using urethral catheters, and 9 Gram-positive and 5 Gram-negative bacteria were identified, with Staphylococcus sp. being the most frequently found bacterium. Antibiotic susceptibility testing showed that Staphylococcus sp., Staphylococcus aureus, and Bacillus sp. were highly sensitive to two antibiotics: doxycycline and meropenem. Conversely, these bacteria showed resistance to several antibiotics, including chloramphenicol. Conclusion: Urethral catheter use revealed Staphylococcus sp. as the most frequently found bacterium. Antibiotic susceptibility testing showed that Staphylococcus sp., Staphylococcus aureus, and Bacillus sp. were sensitive to doxycycline and meropenem.